The Americleft Project: A Comparison of Short- and Longer-Term Secondary Alveolar Bone Graft Outcomes in Two Centers Using the Standardized Way to Assess Grafts Scale. (September 2016) - Ruppel, J.K.; Long, R.E.; Oliver, D.R.; Semb, G.; Russell, K.A.; Mercado, A.M.; Daskalogiannakis, J.; Hathaway, R.R.
Objective: To compare length of follow-up and cleft site dental management on bone graft ratings from two centers. Design: Blind retrospective analysis of cleft site radiographs and chart reviews for determination of cleft-site lateral incisor management. Patients: A total of 78 consecutively grafted patients with complete clefts from two major cleft/craniofacial centers (43 from Center 1 and 35 from Center 2). Interventions: Secondary iliac crest alveolar bone grafting, at a mean age of 9 years 9 months (Center 1: 9 years 7 months; Center 2: 10 years 0 month). Main Outcome Measures: The Americleft Standardized Way to Assess Grafts scale from 0 ( failed graft ) to 6 ( ideal ) was used to rate graft outcome at two time points (T1, T2). Average T1 was 11 years 1 month of age, 1 year 3 months postgraft. Average T2 was 17 years 11 months of age, 8 years 0 months postgraft. Six trained and calibrated raters scored each radiograph twice. Reliability was calculated at T1 and T2 using weighted kappa. A paired Wilcoxon signed rank test ( P < .05) tested T1 and T2 differences for each center. A Kruskal-Wallis test was used to determine the significance of differences between centers at T1 and T2. Correlation tested whether T1 ratings predicted T2. Linear regression determined possible factors that might contribute to graft rating changes over time. Results: Reliability was good at T1 and T2 (interrater = .713 and .701, respectively; intrarater = .790 and .805, respectively). Center 1 scores were significantly better than those from Center 2 at both T1 (5.21 versus 3.29) and T2 (5.18 versus 3.44). There was no statistical difference between T1 and T2 scores for either center; although, there was a greater chance of bone graft score improving with completion of canine eruption and substitution for missing lateral incisors. Conclusions: Short-term ratings of graft outcomes identified significant differences between centers that persisted over time. Dental cleft-site management influenced final graft outcome.